Estimated 24-Hour urinary sodium and potassium excretion in adults in the Northwest Region of Morocco, 2017 - Mohamed Idrissi; Naima Saeid; Samir Mounach; Hicham El Berri; Ayoub Al Jawaldah; Fadoua Rahhaoui; Fatima-Zahra Mouzouni; Anass Rami; Kaoutar Benjeddou; Houria Lahmam; Hasnae Benkirane; Mohammed Elmzibri; et al. (BMC, 2023)
Abstract Background Excessive sodium (Na) and insufficient potassium (K) intake contribute to a high risk of cardiovascular events. Morocco lacks data on actual Na and K intake in adults. We estimated mean Na and K intake in a Moroccan population of adults residing in the Northwest region using 24-h urinary excretion and examined their association with blood pressure (BP). Methods A total of 371 adults from this region, who were recruited for the STEPs Survey Morocco 2017, completed demographic, anthropometric as well as BP data and provided a valid 24-h urine collection according to the standard World Health Organization (WHO) protocol. Multiple Linear Regression analysis was used to examine the association between 24-h urinary sodium (24-hUNa) and 24-h potassium excretion (24-hUK) with BP. Results Mean Na excretion was 2794 mg/day and mean K excretion was 1898 mg/day. Overall, only 114 (30.7%) adults met the WHO recommendation for Na intake (< 2000 mg/d) and 31 (8.4%) met the adequate level for K intake (⩾3510 mg/d). There was no association between 24-hUNa and 24-hUK with BP (P > 0.05 for all). Conclusion Na intake was higher and K intake was lower than WHO recommendations in the study population. There was no association between estimated Na and K intake levels with BP in this population.